PENGOBATAN TRADISIONAL DALAM NASKAH KUNO KOLEKSI SURAU TAREKAT SYATTARIYAH DI PARIANGAN - Wirma Andri (Jurnal Elektronik WACANA ETNIK, 2012)
This article describes sosioculture context in traditional medicines in Surau Terekat Syattariyah manuscript collections. Those objects were analyzed with philology and ethnomedicine approach. The results show that Pariangan population has health and disease context. This society also believes that diseases were caused by spirits interferences besides by physical causes.  Otherwise, traditional medicine in Pariangan can not be separated from religion and magic. This also suggests the combination of tarekat and tradition.